2021
DOI: 10.1136/medhum-2021-012206
|View full text |Cite
|
Sign up to set email alerts
|

“If we can show that we are helping adolescents to understand themselves, their feelings and their needs, then we are doing [a] valuable job”: counselling young people on sexual health in the Brook Advisory Centre (1965–1985)

Abstract: First opened in 1964 in London, the Brook Advisory Centres (BAC) were the first centres to provide contraceptive advice and sexual counselling to unmarried people in postwar Britain. Drawing on archival materials, medical articles published by BAC members and oral history interviews with former counsellors, this paper looks at tensions present in sexual health counselling work between progressive views on young people’s sexuality and moral conservatism. In so doing, this paper makes two inter-related arguments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Between the 1960s and the 1980s, advice columnists also retained their view of sexual intimacy as the glue holding relationships together, rather than sex as a good in and of itself. The model that Chettiar (2016) and Rusterholz (2021) identify as crucial to postwar (sexual) counselling services for young people and married couples survived on magazine problem pages into the 1980s. Indeed, advisors endorsed behaviour often identified as “permissive” precisely because they saw sexual happiness as crucial to healthy, stable relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between the 1960s and the 1980s, advice columnists also retained their view of sexual intimacy as the glue holding relationships together, rather than sex as a good in and of itself. The model that Chettiar (2016) and Rusterholz (2021) identify as crucial to postwar (sexual) counselling services for young people and married couples survived on magazine problem pages into the 1980s. Indeed, advisors endorsed behaviour often identified as “permissive” precisely because they saw sexual happiness as crucial to healthy, stable relationships.…”
Section: Discussionmentioning
confidence: 99%
“…More recent historical scholarship disputes these claims. Rusterholz (2019Rusterholz ( , 2021Rusterholz ( , 2022 has shown that mid-century sexual counselling called on individuals to work actively, stoically and responsibly towards achievement of the emotional openness perceived as necessary to mutual sexual satisfaction in stable heterosexual relationships. This research confirms and extends the analysis of Chettiar (2016), who sees the state-sponsored expansion of marriage counselling and debates on divorce reform as two sides of the same coin; both demonstrate the identification of romantic and sexual relationships, underpinned by psychologised concepts of emotional health, as essential to social stability.…”
Section: Original Researchmentioning
confidence: 99%
“…Editorial also occurred in sexual counselling, with the shift from (male) psychiatrists to (predominantly female) family planning doctors, nurses and relationship counsellors (Irwin 2006;Irwin 2009;Rusterholz 2020). Strikingly, though, Brook Advisory Centre doctors and counsellors learnt to use 'non-emotive' language when talking to clients about pregnancy and termination-this, they believed, was appropriately non-directive and would help clients reach their own decisions, without outside influence (Rusterholz 2021). Indeed, the strategies of emotional management were used for directive counselling approaches too, as methods for managing and disciplining certain health behaviours.…”
Section: Disciplining Emotionsmentioning
confidence: 99%
“…This style of reply was modelled on approaches by British groups such as the Samaritans, Grapevine and Brook. In the Brook Advisory Centres, as Caroline Rusterholz’s article in this special issue shows, counsellors privileged ‘the notion of safety of intercourse over moral considerations about the status of the relationship’ (Rusterholz 2021). O’Brien’s style of replying to letters was also informed by the controversial straight-talking 1978 British sex education book Make It Happy by Jane Cousins.…”
Section: The Ifpa Youth Group and Irish Problem Pagesmentioning
confidence: 99%